Analisis Kesalahan Mahasiswa Dalam Memecahkan Masalah Matematika Pada Pokok Bahasan Anuitas - Devanda, Arcelya; Atha Nabila, Sabika; Sukmawati , Jayanti (CV RIFAINSTITUT, 2023)
This research was conducted by the difficulties experienced by students in solving mathematical problems on the subject of annuities. This study aims to analyze a description of the mistakes made by students in solving annuity problems. This type of research is a descriptive qualitative research. The subjects in this study were 21 students of Economics Mathematics class of 7A1 majoring in Mathematics Education at Universitas Islam Negeri Syarif Hidayatullah Jakarta. The data collection technique used in this study was a written test and documentation of student answers. The instrument used is 8 questions about the subject matter of annuity. Errors made by students were analyzed based on Soedjaji's mathematical objects, namely facts, concepts, principles, and operations. The results of this study obtained the most errors made by students with an average percentage of errors of 8.571%, namely principle errors.